2014
DOI: 10.1093/jhps/hnu010
|View full text |Cite
|
Sign up to set email alerts
|

Can we predict femoral head vitality during surgical hip dislocation?

Abstract: Purpose: Surgical hip dislocation is commonly performed in orthopaedic surgery for several pathologies that often present risk of avascular necrosis (AVN) of femoral head. Observation of blood spilling out from a drill hole, performed in the head after dislocation, has been proposed as a predictive test for AVN. No data have been published about test reliability. Study’s aim was to evaluate the correlation between ‘bleeding sign’ and AVN in surgical dislocation for elective disease and for acetabular fractures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…Of the five patients with AVN, three had no perfusion when tested. This correlation was not observed by Upasani et al, 9 but confirmed by Novais et al 27 and Aprato et al 28 Masquijo et al 8 and Upasani et al 9 correlate complications with the surgeon's learning curve and experience. Our series had 4 AVN cases among the first 10 patients, operated on within the first 5 years, and a single AVN case during the last 5 years.…”
Section: Discussionmentioning
confidence: 75%
“…Of the five patients with AVN, three had no perfusion when tested. This correlation was not observed by Upasani et al, 9 but confirmed by Novais et al 27 and Aprato et al 28 Masquijo et al 8 and Upasani et al 9 correlate complications with the surgeon's learning curve and experience. Our series had 4 AVN cases among the first 10 patients, operated on within the first 5 years, and a single AVN case during the last 5 years.…”
Section: Discussionmentioning
confidence: 75%
“…The drilling test (bleeding sign) is one of the reliable tests to predict the viability of the femoral head in patients who undergo surgical hip dislocation [ 35 , 36 ]. In a study to predict femoral head vitality during surgical hip dislocation, Aprato et al reported that the sensitivity of the drilling test was 97%, while its specificity was 83% [ 35 ]. The test can be performed intraoperatively to determine femoral head viability.…”
Section: Discussionmentioning
confidence: 99%
“…The methods of assessing femoral head perfusion that have been described are evaluation of bleeding by creating a drill hole [ 16 , 29 , 33 ], the use of Laser Doppler Flowmetry [ 17 , 20 ] and intracranial pressure monitoring (ICP) [ 14 , 19 ]. Assessing bleeding via a drill hole is a simple way to assess femoral head perfusion but can only be done with open surgeries.…”
Section: Discussionmentioning
confidence: 99%